2023
DOI: 10.3390/v15020556
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2-Induced TSLP Is Associated with Duration of Hospital Stay in COVID-19 Patients

Abstract: Thymic stromal lymphopoietin (TSLP) is an epithelium-derived pro-inflammatory cytokine involved in lung inflammatory responses. Previous studies show conflicting observations in blood TSLP in COVID-19, while none report SARS-CoV-2 inducing TSLP expression in bronchial epithelial cells. Our objective in this study was to determine whether TSLP levels increase in COVID-19 patients and if SARS-CoV-2 induces TSLP expression in bronchial epithelial cells. Plasma cytokine levels were measured in patients hospitalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…While TSLP showed a numerical increase in COVID-19 patients, statistical significance was not achieved in our study due to the low sample size. Nevertheless, previous research has reported a correlation between TSLP levels and the duration of hospitalization in COVID-19 patients, suggesting a possible role of TSLP in disease progression [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While TSLP showed a numerical increase in COVID-19 patients, statistical significance was not achieved in our study due to the low sample size. Nevertheless, previous research has reported a correlation between TSLP levels and the duration of hospitalization in COVID-19 patients, suggesting a possible role of TSLP in disease progression [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Detecting these cytokines in human samples has been challenging due to their low levels, making them difficult to detect with standard commercial assays. Advanced and sensitive detection methods are needed to accurately measure these cytokines and gain a better understanding of their role in immune responses and diseases like COVID-19 [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mast cell-induced proinflammatory cytokines promote the lung inflammation and cause fever [7] . The hallmark of COVID-19 pathogenesis is the cytokine storm with elevated levels of inflammatory cytokines including tumor necrosis factor-alpha (TNF-α), interleukin (IL)-6, IL-1β, and TSLP [7] , [22] , [23] , [24] . TNF-α is released by mast cells [25] , [26] and considered one of the leading mediators of acute inflammation, the activation of which can also trigger IL-1 and IL-6 production [27] .…”
Section: Discussionmentioning
confidence: 99%
“…They observed that signaling through IRF-3 using TLR3, the agonist of dsRNA, induced TSLP production, which implies that respiratory viral infection induces TSLP production [122]. Gerla et al (2023) cultured NHBE cells and patient bronchoscopyderived primary human bronchial epithelial cells and infected them with SARS-CoV-2. They observed that intracellular and secreted TSLP expression significantly increased with SARS-CoV-2 infection.…”
Section: Epithelial-derived Immune Mediators In Sars-cov-2 Infections...mentioning
confidence: 99%
“…This could contribute to the remodeling and fibrosis of the lungs seen with acute respiratory disease syndrome and accompanied by diffuse alveolar damage [141]. • Induction of acute phase protein response by hepatocytes [104] • Elevated levels of these cytokines are associated with respiratory distress syndrome and severe disease [148] Epithelial-derived alarmins IL-33 [111] TSLP [123] • Promotion of type 2 inflammatory response and inhibition of type 1 responses; associated with requirement for intensive care [129,130] The airway epithelium can secrete IL-13, which is an important mediator involved in repair following injury [115,116]. Plasma IL-13 levels were found to be significantly elevated in COVID-19 patients with severe disease and those requiring mechanical ventilation.…”
Section: Epithelial-derived Immune Mediators In Sars-cov-2 Infections...mentioning
confidence: 99%